SAT0396 IMPROVEMENT IN THE SIGNS AND SYMPTOMS OF PSORIATIC ARTHRITIS WITH IXEKIZUMAB COMPARED TO PLACEBO IN PATIENT SUBGROUPS DEFINED BY BASELINE DISEASE CHARACTERISTICS. (June 2019) - Tony, Hans-Peter; Galindez, Eva; Sprabery, Aubrey Trevelin; Gellett, Amanda M.; Lin, Chen-Yen; Park, So Young; Bertram, Clinton C.; Ogdie, Alexis
Abstract : Background: Ixekizumab (IXE), a high-affinity monoclonal antibody that selectively targets interleukin-17A, was superior to placebo (PBO) in two randomized Phase 3 studies in patients (pts) with active psoriatic arthritis (PsA). 1, 2 Objectives: To assess the consistency of response of IXE across subgroups of pts defined by specific baseline disease characteristics. Methods: Data were analyzed from an integrated database of 2 randomized, double-blind, Phase 3 studies in pts who were either biologic Disease Modifying Anti-Rheumatic Drug (bDMARD)-naïve (SPIRIT-P1) or who had prior inadequate response or intolerance to TNF inhibitors (SPIRIT-P2). Analyses included pts randomly assigned to the approved dosing regimen of IXE (80 mg IXE every 4 wks [IXE Q4W] with a starting dose of 160 mg IXE) or to PBO through Wk 24. Efficacy was measured as the percentage of pts achieving ≥20%, 50%, or 70% improvement from baseline in the American College of Rheumatology criteria (ACR20/50/70) or minimal disease activity (MDA) in subgroups of pts defined by baseline presence of enthesitis, dactylitis, psoriasis body surface area (BSA) involvement (<3% or ≥3%), and c-reactive protein (CRP >6 or ≤6 mg/L). Missing data were imputed by nonresponder imputation. Results: Clinical response rates at Wk 24 in each subgroup are summarized (Table). Significantly (p<0.05) more patients achieved ACR20, ACR50, ACR70, and MDA with IXE compared to placebo across patient subgroups defined by presence of enthesitis, presence of dactylitis, percentage of psoriasis BSA involvement, and by CRP levels at baseline. Conclusion: At Wk 24, IXE was superior to placebo for the treatment of PsA signs and symptoms regardless of baseline presence of dactylitis or enthesitis, BSA involvement, or CRP levels. References: [1] Mease, et al. Ann Rheum Dis. 2017 [2] Nash, et al. Lancet. 2017 Disclosure of Interests: Hans-Peter Tony Consultant for: Eli Lilly and Company, Speakers bureau: Eli Lilly and Company, Eva Galindez: None declared, Aubrey Trevelin Sprabery Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Amanda M. Gellett Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Chen-Yen Lin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, So Young Park Employee of: Eli Lilly and Company, Clinton C Bertram Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda